An Electrical, Thermal and Optical Analysis for Photovoltaic Module using MATLAB (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2025)
Employing renewable energy decreases global warming dramatically. Photovoltaic (PV) electricity is an important renewable energy source for a bright future. Using programming to predict generated power and losses may assist the researcher in improving the response of solar cells. In brief, applying cooling systems with solar cells can play a vital role in enhancing their performance especially in hot locations. This article describes a systematic approach for measuring generated power, the temperature influence on PV electric energy output, and the optical losses. The approach calculation is done by developing a robust simulation model for synchronism with the MATLAB Simulink tool. Furthermore, the system has been validated by experimental and theoretical articles that have been published. Finally, this research compares the benefits of utilizing a cooling strategy for Baghdad city during the summer season.